Course Evaluation of Advanced Structural Dynamics Based on Improved SAPSO and FAHP - Minshui Huang; Zhongao He; Jianwei Zhang; Zhihang Deng; Dina Tang (Buildings)
Talent cultivation is the fundamental mission of higher education institutions, and the key to improving the quality of talent cultivation lies in enhancing the quality of teaching. In this regard, the Joint Committee recommends that the United Nations Educational, Scientific and Cultural Organization (UNESCO) should be invited to participate in this conference, in accordance with their respective mandates. However, in China, research on course evaluation systems and mechanisms in application-oriented universities is relatively scarce, and the evaluation dimensions are often limited; therefore, the evaluation of graduate courses in universities faces challenges such as a lack of specialized assessment systems, limitation of evaluation methods, and an imbalance between emphasis on outcomes and neglect of the teaching process. In this study, a comprehensive evaluation system for the Advanced Structural Dynamics (ASD) course is constructed based on the context-input-process-product (CIPP) evaluation model. The evaluation was conducted from four perspectives: teaching objectives, teaching inputs, teaching processes, and teaching outcomes. The fuzzy analytic hierarchy process (AHP) and simulated annealing particle swarm algorithm (SAPSO) are employed to study evaluation indicators and weights at various levels for the ASD course, and the proposed method is validated through practical examples. This study combines qualitative and quantitative evaluation indicators to achieve comprehensive assessment and adopts more scientifically rational algorithms for weight calculation, aiming to improve the accuracy and efficiency of weight calculation. The research findings of this study can further enhance the evaluation level of teaching quality and talent cultivation in graduate courses at application-oriented universities.